2023
DOI: 10.3389/fpls.2023.1164555
|View full text |Cite
|
Sign up to set email alerts
|

On the usefulness of mock genomes to define heterotic pools, testers, and hybrid predictions in orphan crops

Abstract: The advances in genomics in recent years have increased the accuracy and efficiency of breeding programs for many crops. Nevertheless, the adoption of genomic enhancement for several other crops essential in developing countries is still limited, especially for those that do not have a reference genome. These crops are more often called orphans. This is the first report to show how the results provided by different platforms, including the use of a simulated genome, called the mock genome, can generate in popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 94 publications
1
0
0
Order By: Relevance
“…The same panel also showed diversity in previous studies involving stress conditions due to low doses of nitrogen (Sant'Ana et al 2020) and symbiosis with growth-promoting bacteria (Yassue et al 2021). In addition, a genetic diversity study involving only genomic information grouped these lines into which six clusters (Machado et al 2023), coinciding with the results found in this study (Fig. 2A).…”
Section: Panel Discrimination and Variabilitysupporting
confidence: 89%
“…The same panel also showed diversity in previous studies involving stress conditions due to low doses of nitrogen (Sant'Ana et al 2020) and symbiosis with growth-promoting bacteria (Yassue et al 2021). In addition, a genetic diversity study involving only genomic information grouped these lines into which six clusters (Machado et al 2023), coinciding with the results found in this study (Fig. 2A).…”
Section: Panel Discrimination and Variabilitysupporting
confidence: 89%